(untitled) (CAHIERS MAGELLANES-NS, 2024)
The purpose of the study is to study the peculiarities of the formation of visual activity in preschoolers with hearing impairment. The object of the research is non-traditional methods of formation of visual activity of preschool children with hearing impairment. Using non-traditional ways with preschoolers helps them to better understand the world around them, with the help of such drawings, children express their feelings and emotions. Such activities contribute to the education of a sense of beauty, form hard work, develop fine motor skills of hands, attention, memory.